2020
DOI: 10.1084/jem.20190476
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling identifies caspase-1 as a T cell–intrinsic regulator of Th17 differentiation

Abstract: Dendritic cells (DCs) are critical for the differentiation of pathogen-specific CD4 T cells. However, to what extent innate cues from DCs dictate transcriptional changes in T cells remains elusive. Here, we used DCs stimulated with specific pathogens to prime CD4 T cells in vitro and found that these T cells express unique transcriptional profiles dictated by the nature of the priming pathogen. More specifically, the transcriptome of in vitro C. rodentium–primed Th17 cells resembled that of Th17 cells primed f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 61 publications
1
18
0
Order By: Relevance
“…To this end, it has been shown that NLRP3 functions as a transcriptional regulator of Th2 differentiation as evidenced in a loss‐of‐function (Bruchard et al , ) or gain‐of‐function setting (Braga et al , ). Adding to this, a recent study suggests that caspase‐1 plays a critical role in Th17 differentiation, independent of its catalytic activity (Gao et al , ). While it is difficult to reconcile these different studies into a plausible working model, it has to be considered that differences in cell type, ligands, species, and experimental readouts may account for these results.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, it has been shown that NLRP3 functions as a transcriptional regulator of Th2 differentiation as evidenced in a loss‐of‐function (Bruchard et al , ) or gain‐of‐function setting (Braga et al , ). Adding to this, a recent study suggests that caspase‐1 plays a critical role in Th17 differentiation, independent of its catalytic activity (Gao et al , ). While it is difficult to reconcile these different studies into a plausible working model, it has to be considered that differences in cell type, ligands, species, and experimental readouts may account for these results.…”
Section: Introductionmentioning
confidence: 99%
“…These three signals are necessary to activate and prime antigen-specific T cells, a process that can take several days to complete (Inaba et al, 2000;Jain and Pasare, 2017). On the basis of the initial PRRs engaged by a pathogen, the profile of secreted cytokines from the DCs is also altered to relay information about the nature of the pathogen to naive T cells (Gao et al, 2020;Huang et al, 2001). This pathogen-specific T cell response is critical for the long-term protection against many virulent pathogens (Lo et al, 1999;Bhardwaj et al, 1998;Hess et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…MHC class-I-restricted, ovalbuminspecific, CD8+ T cells from OT-I TCR transgenic mice) and measured the activation and functional phenotypes of T cells after the co-culture with DCs (fig. 2D) (26). While OT-I CD8+ T cells primed with DCs pulsed with all bacteria showed significantly higher activation (fig.…”
Section: Highly Abundant Microbiota Translocators Into Secondary Lymphoid Organs Activate Dcs and Induce Anti-tumor Effector T Cell Respomentioning
confidence: 80%
“…Th1 vs Th17, etc.) (26). In an effort to ascertain whether there was any human clinical data to corroborate our murine findings, we interrogated tumor RNASeq data acquired from 458 human melanoma patients in the Cancer Genome Atlas.…”
Section: Highly Abundant Microbiota Translocators Into Secondary Lymphoid Organs Activate Dcs and Induce Anti-tumor Effector T Cell Respomentioning
confidence: 85%
See 1 more Smart Citation